BAHAYA NARKOBA TERHADAP GENERASI MUDA - Lambang Siswandi; Sarbini Sarbini; Moh Kamaluddin; Wyda Lusiana; Ulfa Rahmawati; Ragil Ira Mayasari; Irwan Swandana; Ana Indrawati (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2022)
Counseling about drug abuse is very important, especially among youth generation. This age period is a group that is prone to drug abuse because of the desire to do experiment, seek identity, seek recognition and lifestyle. The counseling aims to provide knowledge and understanding about the disadvantages of drug abuse, the impact of drug abuse and the legal impact of drug abuse. This counseling is important as a preventive effort to overcome the danger of drugs. Hopefully, the youth generation will be more interested to find out what drugs are and examine the pros and cons without having to try and learn from other’s experience.